Characterization of genes and proteins involved in the absorption of long-chain fatty acids in the gastrointestinal tract of cattle - Hentz, Fernanda; Batistel, Fernanda (Frontiers in Animal Science, 2024)
Dietary fatty acids play a pivotal role in energy metabolism and various physical functions. However, the molecular mechanisms underlying the absorption of long-chain fatty acids (LCFA) in ruminant animals remain poorly understood. To address this gap, we investigated the occurrence and distribution of genes and proteins previously characterized in nonruminant models within the gastrointestinal tract of cattle. Tissue samples from the rumen, descending duodenum, proximal jejunum, medial jejunum, distal jejunum, and distal ileum were collected at slaughter from eight Holstein steers. RT-PCR and capillary electrophoretic-based chemiluminescence were used to determine the mRNA and protein levels of genes and proteins involved in the uptake, activation, intracellular trafficking, re-esterification, and lipoprotein assembly of LCFA. Measurable mRNA levels were found for 38 genes involved in the intestinal absorption of LCFA in all examined sections of the bovine gastrointestinal tract. The mRNA abundances of all genes were greater in the intestinal sections than in the rumen sections (p < 0.05). At the protein level, the expression of nine key transporters and enzymes, namely, CD36, SLC27A4, ACSL1, FABP1, FABP2, DGAT1, MTP, Apo-AI, and ACAT2, was detected in most of the intestinal sections. The distribution profile of these proteins in the small intestine suggested a prominent role for protein-mediated absorption of LCFA in the proximal and distal intestine in cattle. The low expression levels of most proteins in the rumen suggest little absorption of LCFA at this location in cattle. Overall, the findings from this study support the presence, in cattle, of genes and proteins involved in the intestinal absorption of LCFA described in models of nonruminants. Identifying the proteins involved in the absorption of LCFA in the small intestine is the first step in understanding how the expression of these proteins influences the capacity of the small intestine to absorb fatty acids in cattle.